A survey of the dialect geography in the six towns of Camarines Norte Capalonga, Jose Panganiban, Vinzons, Talisay, Daet and Basud - Ella, Lilia Octa 1933- ([Quezon City s.n.], 1970)
The aim of the study is to conduct a survey of the dialect geography of the six towns of Camarines Norte namely: Capalonga, Jose Panganiban, Vinzons, Talisay, Daet and Basud. It is primarily concerned with finding the differences in forms of words having similar meanings. Results show that Camarines Nore is divided into two speech communities. In the Northern municipalities of the province, Tagalog is dominant while in the southern towns, Bicol dominates. It was also noted that word variations exist in the different towns of the two speech communities.
Thesis (M.A.T.Pilipino)--University of the Philippines
Typescript
Keywords: Bikol language -- Dialects; Camarines Norte -- Languages -- Maps